URGENSI FATWA MAJLIS ULAMA INDONESIA (MUI) BAGI UMMAT ISLAM INDONESIA - Zenal Setiawan (LPPM-IAI BATAM, 2023)
The Fatwa of the Indonesian Ulema Council (MUI) has a high urgency for Muslims in Indonesia. As an authoritative institution with recognized religious expertise, MUI has a central role in providing religious guidelines relevant to Indonesia's socio-political situation and context. In this background, this article discusses the urgency of the MUI fatwa in the context of Indonesian Islamic community. First, MUI fatwa is important in responding to the development of contemporary times and issues. The fatwa provides an interpretation of Islamic law that considers Indonesia's religious values, humanitarian principles, and social context. It helps Muslims understand and deal with issues such as technology, economics, bioethics, and emerging social issues. Second, MUI fatwa plays an important role in maintaining the unity of Muslims. In diverse societies, the MUI fatwa provides guidelines accepted by the majority of scholars and Muslims in Indonesia. It helped to reach an understanding and consensus in understanding and practicing religious teachings, preventing division and conflict between Muslims. Furthermore, MUI fatwa has a wide impact on people's lives. The fatwa is used as a reference in the process of creating laws, government policies, and religious courts. It forms a legal and regulatory order that conforms to Islamic teachings, and affects people's lives in general. In addition, in the increasingly advanced digital era,